Production of hydrogen from glucose by LaFeO3 based photocatalytic process during water treatment. (12th January 2016) - Iervolino, G.; Vaiano, V.; Sannino, D.; Rizzo, L.; Ciambelli, P.
Abstract: In this work the hydrogen production from photocatalytic degradation of glucose aqueous solution using LaFeO3 catalysts was investigated under UV or visible light irradiation by light-emitting diodes (LEDs). Different LaFeO3 catalysts were prepared by solution combustion synthesis, starting from lanthanum nitrate and iron nitrate aqueous solution, and different amounts of citric acid as organic fuel. The influence of light irradiation and amount of citric acid was evaluated. The photocatalysts were characterized by different techniques, such as XRD, BET, UV–Vis DRS and Raman spectroscopy. As the amount of citric acid was increased from 0.86 to 2.15 g, the specific surface area of perovskite was increased from 4 to 24 m 2 /g, with crystallite size of 38 and 6 nm, respectively. Moreover, the different amounts of citric acid induced changes in the crystallinity degree of LaFeO3 perovskite. LaFeO3 catalyst prepared with a double amount of citric acid (1.72 g) compared to the initial content (0.86 g), was the most active in the photocatalytic production of H2 (up to 1.6 mmol/gcat after 4 h of UV irradiation, corresponding to 16% of hydrogen yield). With this photocatalyst the simultaneous degradation of glucose was 73% after 4 h of UV irradiation. These results are encouraging with respect to the possibility to produce hydrogen during photocatalytic treatment of sugar-containing water by using photocatalysts in the absence of noble metals. Highlights: Hydrogen production from degradation of glucose solution on LaFeO3 . LaFeO3 preparation with different amount of citric acid. High hydrogen production with UV and Visible LEDs. Reaction mechanism of degradation of glucose and hydrogen production.